2014
DOI: 10.1038/ejcn.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance phase angle predicts muscle function, quality of life and clinical outcome in maintenance hemodialysis patients

Abstract: For the MHD population, PA emerged as a useful predictor for impaired muscle function, health-related Qol, upcoming hospitalizations and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
81
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 40 publications
6
81
1
4
Order By: Relevance
“…Inflammation can cause an increased capillary leak and increased ECW, and inflammation can also lead to a reduction in cell mass, and therefore, ICW [34] . Our results are in keeping with other reports using single frequency bioimpedance, demonstrating an association with overhydration and increased mortality [35] , and others recording an association between an increased markers of inflammation and muscle weakness [33,36] .…”
Section: Discussionsupporting
confidence: 93%
“…Inflammation can cause an increased capillary leak and increased ECW, and inflammation can also lead to a reduction in cell mass, and therefore, ICW [34] . Our results are in keeping with other reports using single frequency bioimpedance, demonstrating an association with overhydration and increased mortality [35] , and others recording an association between an increased markers of inflammation and muscle weakness [33,36] .…”
Section: Discussionsupporting
confidence: 93%
“…Body composition in patients with CKD is characterized by excess ECW content associated with sodium retention and a decreased body cell mass with malnutrition, and we speculated that cell volume might be associated with nutritional status and indicate the reserve capacity for volume overload in patients with fluid volume imbalance [40,41]. In fact, the bioimpedance phase angle, as a measure of nutritional status [42,43], was associated with GNRI levels. Hyperphosphotemia is an independent risk factor for adverse outcomes in patients with CKD [44], and serum phosphorus level depends on protein intake [5].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PhA has been associated with a number of clinical conditions, such as advanced liver fibrosis in patients chronically infected with hepatitis C virus [3], cancer [4], peritoneal dialysis [4], malnutrition [5], low muscle mass [6,7], and higher mortality in patients with several diseases [8][9][10]. Recently, in hemodialysis patients, it was also observed that PhA values were associated with muscle function and overall quality of life [11].…”
Section: Introductionmentioning
confidence: 99%